2013
DOI: 10.1021/jo402078q
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Mediated Dehydrogenative Biaryl Coupling of Naphthylamines and 1,3-Azoles

Abstract: A copper-mediated dehydrogenative biaryl cross-coupling of naphthylamines and 1,3-azoles has been developed. The key to its success is the introduction of N,N-bidentate coordination system based on the picolinamide directing group. The reaction proceeds smoothly without precious transition metal catalysts and provides highly π-extended heterobiaryls directly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(39 citation statements)
references
References 112 publications
0
38
0
1
Order By: Relevance
“…Along with the arylation, the group of Punniyamurthy reported a copper catalyzed C8‐introduction of indoles, pyrazoles and pyrroles, while the group of Miura developed a copper‐mediated C8‐azolation of naphthylamines (Scheme ) …”
Section: C8‐functionalization Of Naphthalene Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the arylation, the group of Punniyamurthy reported a copper catalyzed C8‐introduction of indoles, pyrazoles and pyrroles, while the group of Miura developed a copper‐mediated C8‐azolation of naphthylamines (Scheme ) …”
Section: C8‐functionalization Of Naphthalene Derivativesmentioning
confidence: 99%
“…Along with the arylation, the group of Punniyamurthy reported a copper catalyzed C8-introduction of indoles, pyrazoles and pyrroles, [19] while the group of Miura developed a copper-mediated C8-azolation of naphthylamines (Scheme 8). [20] Naphthylamines are compatible with a lot of CÀ H activation reactions and, for instance, Ilies and Nakamura reported an iron-catalyzed methylation of naphthylamide 12 with trimethylaluminium as alkylating agent (Scheme 9). [21] C8-methylated naphthalene 15 was isolated in an excellent yield of 97 %.…”
Section: Bidentate Directing Groups: Picolinamide Derivativesmentioning
confidence: 99%
“…[10] Optimization studies revealed that the use of acid as additive was essential for the reaction to take place.A mong the various carboxylic acids screened, PivOH provedt ob et he most effective one. Notably,t he direct arylation occurred site-selectively at the C-8 positiono f1 -naphthylamide but not at the position ortho to the amide group,p ossibly resulting from the preferable formation of af ive-membered metallacycle.…”
Section: Scheme2screeningo Fdirectinggroupsmentioning
confidence: 99%
“…The related dehydrogenative biaryl couplings of indoles, benzamides, and naphthylamines also proceed in the presence of Cu(OAc) 2 , with the assistance of appropriate directing groups, to make the corresponding bi(hetero)aryl linkages efficiently (Eqs. 15-17) [35][36][37]. The directors except for the 2-phenylpyridine are readily attachable and detachable: 2-pyrimidyl (Eq.…”
Section: Arylationmentioning
confidence: 99%